Analysis of The State Civil Apparatus Commission Relating to Position Selection and Return of Tasks From the State Civil Apparatus Commission to the Ministry of State Administrative and Bureaucratic Reform - Hidayah, Ahmad (INDONESIAN JOURNAL OF SUSTAINABILITY, 2023)
Currently, the law that is being intensively revised or changed is Law Number 5 of 2014 concerning ASN (State Civil Apparatus Law). Minister of State Apparatus Empowerment and Bureaucratic Reform (Menpan-RB) Yuddy Chrisnandi stated that it is important to reform the management of the State Civil Apparatus (ASN) to realize good governance in order to face the ASEAN Economic Community (AEC). The general picture is that the services provided by the apparatus to the community are still low in terms of administration, such as licensing, which is still convoluted and complex. The incessant coverage in various mass media regarding corrupt practices by the state apparatus is also proof that the bureaucratic reform that has been rolled out is still far from expectations. This is compounded by the widespread practice of bureaucratic politicization in government circles in general, especially in regional government because the system of appointing officials in government institutions tends to provide opportunities.